2006
DOI: 10.1007/s10562-006-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Pt–Ni/γ-Al2O3 catalyst for the preferential CO oxidation in the hydrogen stream

Abstract: The preferential CO oxidation (PROX) in the presence of excess hydrogen was studied over Pt-Ni/c-Al 2 O 3 . CO chemisorption, X-ray diffraction, transmission electron microscopy, energy dispersive X-ray spectroscopy and temperature-programmed reduction were conducted to characterize active catalysts. The co-impregnated Pt-Ni/c-Al 2 O 3 was superior to Pt/Ni/c-Al 2 O 3 and Ni/Pt/cAl 2 O 3 prepared by a sequential impregnation of each component on alumina support. The PROX activity was affected by the reductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…e order of CO chemisorption capacity of the catalysts is Pt > PtCo > PtNi. ese results coincide with the reports of Ko et al [21] which indicate that the addition of Ni to Pt/Al 2 O 3 catalysts decreases the number of accessible sites for CO adsorption, though it improves the activity for preferential CO oxidation in the presence of H 2 . e CO chemisorption capacity of the NiCo-UMC catalysts is similar to that of the monometallic Pt catalysts, but the metal concentration of the latter is six times greater.…”
Section: Catalysts Characterizationsupporting
confidence: 91%
“…e order of CO chemisorption capacity of the catalysts is Pt > PtCo > PtNi. ese results coincide with the reports of Ko et al [21] which indicate that the addition of Ni to Pt/Al 2 O 3 catalysts decreases the number of accessible sites for CO adsorption, though it improves the activity for preferential CO oxidation in the presence of H 2 . e CO chemisorption capacity of the NiCo-UMC catalysts is similar to that of the monometallic Pt catalysts, but the metal concentration of the latter is six times greater.…”
Section: Catalysts Characterizationsupporting
confidence: 91%
“…There is a pronounced influence on the NiO reduction temperature for the Pt-Ni-Al sample following the addition of Pt. The reduction temperature shifts to a lower temperature, attributed mainly to the change in mechanism of the NiO reduction [21,29,30].…”
Section: Temperature Programmed Reductionmentioning
confidence: 99%
“…The increase in the broadness and peak shoulder at 670 °C could be an indication that NiO particles are loosely bound to the support, and these particles saturate the surface of the support forming bulk NiO [28]. For the mono-metallic Pt-Al catalyst, a broad reduction peak is observed at around 350 °C, which can be assigned to the reduction of platinum oxide to its metallic form [29]. There is a pronounced influence on the NiO reduction temperature for the Pt-Ni-Al sample following the addition of Pt.…”
Section: Temperature Programmed Reductionmentioning
confidence: 99%
“…However, the activity depends critically on the particle size and is hence susceptible to sintering [4]. Other materials investigated include Ru [5], RuO 2 [6], CuO/CeO 2 [7], Pd [8], Pt [9,10], and alloys such as Al 1 Mn 6.7 Co, and Ag 3.3 Mn 34.1 Co 1.7 Ni [11]. Recent research has shown that hydrous ruthenium oxide is a very active catalyst for the oxidation of CO.…”
Section: Introductionmentioning
confidence: 99%